ELECTRON BEAM THERAPY OF MYCOSIS FUNGOIDES - Bagshaw, Malcolm A. (1961)
Ionizing radiation in the form of x-ray therapy is the best modality of treatment available at the present time for single, isolated lesions of mycosis fungoides. However, for generalized mycosis fungoides, generalized x-ray therapy is technically difficult and dangerous. It is now possible to employ electron beam therapy for generalized mycosis fungoides, using energies which confine the dose to the superficial layers of the skin and thus avoid hematopoietic injury. A technique for wide field electron beam therapy has been developed for this purpose which has been effective and well tolerated in limited trials to date.